Levels of Perfluorooctane Sulfonate in the Beaufort Sea Shelf Food Web: Modelling Impacts of Climate Change and Implications for Human Health - Wallace, Helen (Université d'Ottawa | University of Ottawa, 2024)
Perfluorooctane sulfonate (PFOS) is a persistent organic pollutant of global concern due to its capacity to bioaccumulate, biomagnify, and cause adverse human health effects. It is ubiquitous in the Arctic environment, particularly biota, and PFOS exposure for Inuit has been associated with the consumption of marine country foods such as beluga and ringed seals. Climate change can increase the exposure to and bioaccumulation of pollutants in marine organisms, partly through the alteration of ecosystem trophodynamics. To date, there has been limited research on dietary exposure to contaminants via marine country foods for Inuvialuit in the Western Arctic relative to other regions of Inuit Nunangat, particularly in the context of future climate changes. Further, modelling of climate change induced changes to trophodynamics and subsequent impact to contaminants in marine ecosystems has not examined any perfluoronated compound, including PFOS. To address these gaps, ecological modelling software Ecopath with Ecosim was used to assess PFOS concentrations in the Beaufort Sea Shelf marine food web under two climate change scenarios. Projected sea surface temperature and sea ice cover data for the Beaufort Sea corresponding to IPCC AR6 Shared Socioeconomic Pathways (SSP) 1-2.6 and 5-8.5, representing respective low (2°C of warming) and high (4°C of warming) carbon emission scenarios, were used to inform the climate change scenarios. Empirical toxicokinetic and environmental concentration data for PFOS were used to simulate the model area as of the model start year 2010. Model bias analysis indicates that the model simulates PFOS concentrations fairly representative of the species with available data, with model bias values ranging from 0.01-1.7. The projected amplification of PFOS in key species was between 9-19% and 11-30% by 2100 under SSP1-2.6 and SSP5-8.5, respectively, relative to a no-climate change control scenario. These projected PFOS concentrations under each climate change scenario correspond to marginal increases in dietary iv exposure to PFOS for Inuvialuit from beluga, Arctic char, and whitefish consumption compared to no climate change. Hazard quotients (HQ) for the dietary exposure to PFOS from these country foods remain low; HQ <0.01, indicating that any increases in PFOS concentrations in key country foods driven by climate change are unlikely to pose a health risk to the population level for this region. As this modelling approach has not yet been used for perfluoroalkyls, this study serves as a first attempt at building a model for PFOS and provides novel insight into the impacts of climate change on this class of compounds. The findings from this study may also be useful to Inuvialuit communities for making informed health decisions, prioritization for country food biomonitoring programs, and developing climate change adaptation plans.
Keywords: Climate change; Contaminants; Toxicology; Human health risk assessment